Long‐term safety and efficacy results in hepatitis C virus genotype 1‒infected patients receiving ombitasvir/paritaprevir/ritonavir + dasabuvir ± ribavirin in the TOPAZ‐I and TOPAZ‐II trials. Issue 5 (17th February 2020) - Poordad, Fred; Castro, RuiSarmento E.; Asatryan, Armen; Aguilar, Humberto; Cacoub, Patrice; Dieterich, Douglas; Marinho, Rui Tato; Carvalho, Armando; Siddique, Asma; Hu, Yiran Bonnie; Charafeddine, Mariem; Bondin, Mark; et al.
Abstract: The 3‐DAA regimen consisting of ombitasvir/paritaprevir/ritonavir plus dasabuvir (OBV/PTV/r + DSV) ± ribavirin (RBV) has shown high sustained virologic response rates (~95%) in phase 3 clinical trials including >2300 HCV genotype 1–infected patients. Real‐world evidence studies have confirmed the effectiveness of OBV/PTV/r ± DSV ± RBV in patients with chronic HCV genotype 1 infection and are consistent with clinical trial results. TOPAZ‐I and TOPAZ‐II are ongoing phase 3b trials, assessing safety, efficacy and long‐term progression of liver disease and clinical outcomes for up to 5 years post‐treatment in patients treated with OBV/PTV/r + DSV ± RBV. High rates of sustained virologic response (SVR) were achieved regardless of presence or absence of cirrhosis.In this report, we assessed the long‐term progression of liver disease and incidence of clinical outcomes up to 3 years of post‐treatment follow‐up in patients with chronic HCV GT1 infection who were treated with (OBV/PTV/r + DSV) ± RBV in the TOPAZ‐I and TOPAZ‐II studies. Improvements were observed in liver disease markers including FIB‐4, METAVIR and Child‐Pugh scores as well as platelet counts. Clinical outcomes related to long‐term progression of liver disease such as liver decompensation were infrequent (<1%). Hepatocellular carcinoma (HCC) occurred in 1.4% of cirrhotic patients.